Mitochondrial membrane potential-enriched CHO host: a novel and powerful tool for improving biomanufacturing capability. Issue 1 (31st December 2022) - Chakrabarti, Lina; Chaerkady, Raghothama; Wang, Junmin; Weng, Shao Huan Samuel; Wang, Chunlei; Qian, Chen; Cazares, Lisa; Hess, Sonja; Amaya, Peter; Zhu, Jie; Hatton, Diane
ABSTRACT: With the aim of increasing protein productivity of Chinese hamster ovary (CHO) cells, we sought to generate new CHO hosts with favorable biomanufacturing phenotypes and improved functionality. Here, we present an innovative approach of enriching the CHO host cells with a high mitochondrial membrane potential (MMP). Stable transfectant pools and clonal cell lines expressing difficult-to-express bispecific molecules generated from the MMP-enriched host outperformed the parental host by displaying (1) improved fed-batch productivity; (2) enhanced long-term cell viability of pools; (3) more favorable lactate metabolism; and (4) improved cell cloning efficiency during monoclonal cell line generation. Proteomic analysis together with Western blot validation were used to investigate the underlying mechanisms by which high MMP influenced production performance. The MMP-enriched host exhibited multifaceted protection against mitochondrial dysfunction and endoplasmic reticulum stress. Our findings indicate that the MMP-enriched host achieved an overall "fitter" phenotype that contributes to the significant improvement in biomanufacturing capability.